Membranes and deoxyribonucleic acid of hippocampal neurons damage due to low-density polyethylene microplastics in blood of Wistar rats - Sincihu, Yudhiakuari; Sudiana, I Ketut; Kusumastuti, Kurnia; Keman, Soedjajadi; Sulistyorini, Lilis; Lusno, Muhammad Farid Dimjati; Mohd Elias, Saliza; Siti Nur Hasina (Universidad Tecnica de Manabi, 2022)
Microplastic particles in the blood can cause damage to organs such as the brain. This study aimed to analyze the effect of microplastic particles in the blood on membrane damage (expression of malondialdehyde metabolites) and deoxyribonucleic acid damage (expression of 8-hydroxy-2′-deoxyguanosine metabolites) in hippocampus neurons of Wistar rats. Methods: Forty-two Wistar rats were used and equally divided into six groups. The study groups X1, X2, X3, X4 and X5 was given 0.0375mg, 0.075mg, 0.15mg, 0.3mg, and 0.6mg of low-density polyethylene microplastic powder mixed with 2cc distilled water respectively, while the control group only given distilled water. Microplastic administration was carried out for 90 days. Results: Microplastic particles were found in the blood of Wistar rats. The level of microplastics particle was higher along with the higher exposure dose. The mean expression of malondialdehyde and 8-hydroxy-2′-deoxyguanosine metabolites in the hippocampal neurons in CA1 and CA3 areas were significantly increased with higher exposure doses (Kruskal-Wallis test p <0.01). The Spearmen’s correlation showed a strong relationship between the levels of microplastic particles in blood and the expression of metabolites malondialdehyde and 8-hydroxy-2′-deoxyguanosine (all p <0.01). Microplastic in the blood of Wistar rats has increased expression of malondialdehyde and 8-hydroxy-2′-deoxyguanosine metabolites in hippocampal neurons.